Passion Karyawan dalam Turnover Intention (Journal of Hospital Management, 2019)
Turnover is a classic problem in HR management that employers do not want. Turnover can be detrimental to the company both in terms of cost, resources, and employee work motivation. Turnover Intention can be influenced by many things, such as the absence of job satisfaction caused by work motivation. The purpose of this study is to get empirical evidence of organizational culture variables on job satisfaction, organizational commitment to job satisfaction, motivation on job satisfaction, job satisfaction on turnover intention, organizational culture towards turnover intention, organizational commitment to turnover intention and motivation for turnover intention in Antam Medika Hospital Jakarta employees. This research method is a quantitative study with a research instrument used in the form of a questionnaire, data obtained through a questionnaire filled out by respondents. The population in this study was 315 employees of Antam Medika Hospital consisting of 5 different units namely medical services, medical support, nursing, back office and front liner. The number of respondents as many as 180 people were obtained based on the calculation of SEM-AMOS analysis requirements, namely the number of indicators at times 5-10. Respondents are limited to employees who have worked> 1 year at Antam Medika Hospital. determination of the number of respondents using the cluster system, the time of the study lasted for 1 month from March 1-30 2019. The variables used were 5 variables; organizational culture, organizational commitment, work motivation, job satisfaction and turnover intention. The analytical tool used is SEM. The results showed that organizational culture and motivation affect employee job satisfaction at Antam Medika Hospital with a positive direction, organizational culture and motivation and job satisfaction affect turnover intention at Antam Medika Hospital with a negative direction, and organizational commitment does not affect job satisfaction and turnover intention at Antam Medika Hospital. The findings obtained by work motivation indicate that in order to reduce the tuning intention of employees at Antam Medika Hospital, it is necessary to review the factors that have been proven to influence among them organizational culture, work motivation and employee job satisfaction. While Organizational commitment does not have an influence on tunrover intention at Antam Medika Hospital. Keyword: Organizational Culture, Organizational Commitments, Work Motivation, Work Satisfaction, Turnover Intention.